Kobieta trendy – czyli o maltretowaniu ciała - Lewicka, Karolina (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2006)
The history of women is the history of the struggle to look attractive, starting with Egyptian wooden pillows that were to protect hairdos, through to Japanese tied-up feet or the lacing of French beauties’ stays, to silicon bags implanted under the skin of breasts. It is interesting that although the canon of beauty has changed, the mechanisms of the phenomenon has remained unchanged throughout the centuries and has been working like well-greased cogs of discipline, flexibility and pain. If one becomes convinced that the body one has is exactly how it should be, one can cut the Gordian knot of a modern Barbie. To understand this always leads to acceptance and, in this case, to the acceptance of one’s own body, and – consequently – of oneself. However, the body has been subjected to the dictates of modern consumption and patriarchal culture, whose sole purpose is a maximum control over the way women act and think.
A trendy woman, or about body torturing